Novel of comparison between 3d high definition maps created by photogrammetry and laser scanning applied for an autonomous vehicle - Ho, Nang Xuan (Vietnam Journal of Science and Technology, 2021)
In this paper, based on the selected mathematical algorithm, the performing of two methods for building high-resolution 3D maps that are Photographmetry and Laser scanning was analyzed to find out the advantages and disadvantages of each one. The results showed that the high-resolution map constructed by using lidar was more accurate and detailed, whereas the map constructed by using images with coordinates was more intuitive. A mapping method using lidar-camera fusion was proposed in which the detailed roads are created by Lidar and the rest area built by optical imaging method.